An ADMM approach for unit commitment with considering dynamic line rating - Dai, Jiang; Tian, Nianjie; Zhao, Qian; Tang, Chong; Xuan, Peizheng; Cheng, Lanfen (Frontiers in Energy Research, 2024)
In an effort to augment the transmission capabilities within power system scheduling computations, this paper introduces a multi-scenario unit commitment model that incorporates dynamic transmission line capacities, alongside a dedicated Lagrangian relaxation algorithm designed to solve this model. Initially, leveraging the concept of quantile regression, we construct a data-driven model for dynamic transmission line capacity augmentation, grounded in historical environmental parameter datasets. Subsequently, this dynamic transmission line model is integrated into the multi-scenario unit commitment framework, thereby developing a comprehensive unit commitment model that explicitly acknowledges the dynamic nature of transmission line capacities. Ultimately, the system constraints within our model are relaxed, and dynamic transmission line constraints are effectively decoupled through the application of the Alternating Direction Method of Multipliers (ADMM). This allows the dual problem to be decomposed into a series of sub-problems, which are tackled through an iterative algorithm until convergence is achieved. The effectiveness of the proposed model and algorithm is validated using the IEEE-118 and IEEE-300 cases.Indices for units t Indices for time periods s Indices for scenarios b Indices for buses ui,t, di,t Startup and shutdown variable of thermal unit i in time period t xi,t Status variable of thermal unit i in time period t Pi,t,s Power output variable of thermal unit i in time period t under scenario s f Running cost function of thermal unit i π Scenario probability function 1